Pengembangan Lagu untuk Anak Usia Dini 4 - 6 Tahun - Rina Wulandari (Fakultas Ilmu Pendidikan UNY, 2011)
The background of this -researchproblem is the song of children who are less in accordance with the delivery of child development. Therefore, the need to develop model song creations of children, particularly children aged 4-6 years. Based on field observations, there are still songs that are vulnerable to optimize the achievementof the development of music. Through literature studies produced examples of the rhythm patterns, melodies, and poems that close support to optimize child development achievements in the field of music. Key words: development, songs, children aged 4-6 years